Tobacco and Oral Health - Kumar, Jayaprakash; Kushwaha, Sumedha; Tomar, Aditi; Ramanna, Thanuja; Prabhakar, Ishan; Chaudhry, Monica (The Journal of Dentists, 2015)
Tobacco is a menace in all its forms that disrupts the socio economic fabric of our country obstinately. It has affected all the strata of society equally. It has numerous adverse affects on the human health. Preceding systemic effects, oral symptoms are manifested due to direct contact and long term exposure with the product. Various precancerous and cancerous lesions and conditions are evident which are mostly preventable. Correct diagnosis at the correct time becomes essential to a good prognosis. Harmful effects from second and third hand can be reduced if the legislation against tobacco users becomes stronger and stricter.